GUGATAN CLASS ACTION DALAM PENEGAKAN HUKUM PENYELESAIAN HUBUNGAN INDUSTRIAL (STUDI PUTUSAN PENGADILAN NEGERI NOMOR 16/PHI.G/2009/PN Mks. Junto PUTUSAN MAHKAMAH AGUNG NOMOR 304 K/PDT.SUS/2012 - Hidayat Dwi Prasetiamoko, Asna Surya Kusuma, Ismail, Edrian Renanda (GEMA, 2015)
This study aims to find out what the criteria of class action in a dispute resolution of industrial disputes which related to the appeal filed labor group PT. INCO Tbk. through the class action and to find out the reason for the Supreme Court rejected the petition. The method used in the writing are as follows: normative research, the descriptive nature of the research, the approach of cases, legal materials analysis techniques with deductive method, the collection of legal materials to the study of literature concerning or relating to the legal issues, primary legal materials and secondary legal materials were inventoried. Based on the research and discussion done produced the conclusion that the class action has four criteria (4), namely: Numeriousity, commonality, typicality and adequacy of representation and the criteria have been met by the applicant appeal the group workers of PT. INCO Tbk. The Supreme Court subsequently rejected the appeal filed by a group workers of PT. INCO Tbk. with the decision having judex facti not mistaken, the class action mechanism is not known in the Industrial Relations Court and judex facti in this case is not contrary to law and / or the Act